Attitude towards mobile learning among resident doctors involved in undergraduate medical education at a government medical college in Delhi, India - Saurav Basu; Yamini Marimuthu; Nandini Sharma; Pragya Sharma; Navya Gangadharan; Sahadev Santra (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: There is growing recognition of the role of mobile learning (M-learning) for undergraduate (UG) academic education and teaching purposes, but teacher attitudes toward it can be variable. OBJECTIVE: To determine the attitudes toward the incorporation of M-learning methods for UG medical education among resident doctors at a government medical college in Delhi, India. METHODS: A cross-sectional study was conducted for 3-months duration (2019) among 60 final year junior and senior resident doctors. The participants were selected from all the preclinical and paraclinical department, and one clinical department selected randomly based on the probability proportion to size method. The data was collected using self-administered instruments including the modified 20-item M-learning Perception Scale (MLPS). RESULTS: Social media (36.7%) and instant messaging platforms (85%) were routinely used by the participants for exchanging academic (medical) and health-related information. The mean score for all the MLPS item responses was >3, indicating positive attitudes toward M-Learning. The participants expressed maximum agreement with the views stating M-Learning can "supplement traditional teaching," was "reliable for personal use," and "improves the quality of lessons." The responses of those participants having preexisting familiarity with health information and education portals, and those aware of massive open online courses correlated significantly with higher MLPS scores. CONCLUSION: M-learning is visualized as an increasingly relevant teaching and learning medium by early-career resident doctors involved in UG medical education in India.